Do unto others: on the importance of reciprocity in public administration - Oliver, Adam (2018)
There is an extensive literature across the humanities and social sciences on reciprocity as a fundamental driver of human behavior, and yet attempts to bring the main arguments from the diverse literatures together in a single interdisciplinary space remain scarce. This article aims to collate many of the main arguments from these literatures with the intention of speculating how reciprocity might be used to inform institutional structures, management practices, and public policy. This is significant, because the recent literature on public sector policy design tends to attach import to entirely self-regarding and/or altruistic motivations as fundamental drivers of human action, but, with some notable exceptions, says little directly on the role that reciprocity might have to play in motivating performance improvements. The lack of attention paid to reciprocity in the literature on human motivation and public policy design is problematic if one concludes that reciprocating behaviors are a major determinant of group cooperation and success. - Reproduced.
Keywords: Altruism; Motivation; Public administration